2021
DOI: 10.1021/acs.chemmater.1c02615
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors of Diarylethene for a High-Performance Photoprogrammable Polymer Transistor: Crystallographic Compatibility, Quantum Yield, and Fatigue Resistance

Abstract: We show that crystallographic compatibility, quantum yield, and fatigue resistance are three important factors that diarylethene (DAE) should simultaneously satisfy to realize high-performance photoprogrammable polymer field-effect transistors (FETs). The enhancement of crystallographic compatibility achieved by locating DAE preferentially in the vicinity of intercrystallite tie chains is mainly dependent on the overall molecular volume of DAE. The quantum yield of DAE for photocyclization is dependent on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…The closed‐ring isomer of D1a has an adequate HOMO level for trapping holes of several p‐type polymeric OSCs. [ 114 ] To yield high photoprogrammable fatigue resistance and photoprogrammable switching ratio, five different DAE (D1)—D1a, D1b, D1c, D1d, and D1e—were synthesized and studied using well‐known high mobility p‐type polymer DPPT‐TT. All DAE were functionalized with only alkyl substituents so that energy level was unaltered.…”
Section: Semiconductor Trap‐level Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The closed‐ring isomer of D1a has an adequate HOMO level for trapping holes of several p‐type polymeric OSCs. [ 114 ] To yield high photoprogrammable fatigue resistance and photoprogrammable switching ratio, five different DAE (D1)—D1a, D1b, D1c, D1d, and D1e—were synthesized and studied using well‐known high mobility p‐type polymer DPPT‐TT. All DAE were functionalized with only alkyl substituents so that energy level was unaltered.…”
Section: Semiconductor Trap‐level Controlmentioning
confidence: 99%
“…The energy of the conduction band minimum (CBM) of WSe 2 was located between that Reproduced with permission. [114] Copyright 2021, American Chemical Society.…”
Section: Control Of Semiconductor Trap-level In Organic Fet Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21] This approach has a significant advantage in terms of imparting structural simplicity over strategies involving the use of other organic memory devices such as floating-gate-or electret-based OFETs, because only the channel layer is slightly tuned from a single-component organic semiconductor to an organic semiconductor/molecular switch mixture, while all other constituting layers of OFETs can be the same. [22][23][24][25][26][27] This advantage has led many researchers to attempt to realize high-performance photoprogrammable OFETs with various combinations of organic semiconductors and molecular switches. For example, Samori et al reported photoprogrammable OFETs employing several organic semiconductors mixed with cyclopentene-based DAE derivatives, resulting in outstanding photoprogrammable I DS ON/OFF ratios of over 10 2 (the photoprogrammable I DS ON/OFF ratio is defined as |I DS (DAE_o)|/|I DS (DAE_c)|).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Samori et al reported photoprogrammable OFETs employing several organic semiconductors mixed with cyclopentene-based DAE derivatives, resulting in outstanding photoprogrammable I DS ON/OFF ratios of over 10 2 (the photoprogrammable I DS ON/OFF ratio is defined as |I DS (DAE_o)|/|I DS (DAE_c)|). [22][23][24][25][26][27][28][29] There have also been reports on optimizing the chemical structures of DAEs to further enhance the photoprogrammable I DS ON/OFF ratios. 27 One notable point from these previous studies illustrates that typical diketopyrrolopyrrole (DPP)-based copolymers, which are known to have high charge carrier mobilities, are not suitable in terms of photoprogramming stability for most DAEs due to their excessively high crystalline nature.…”
Section: Introductionmentioning
confidence: 99%